2021
DOI: 10.3390/jcm10204679
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Maternal Urine for the Early Detection of Preeclampsia and Fetal Growth Restriction

Abstract: Background: To explore the use of maternal urine proteome for the identification of preeclampsia biomarkers. Methods: Maternal urine samples from women with and without preeclampsia were used for protein discovery followed by a validation study. The targeted proteins of interest were then measured in urine samples collected at 20–24 and 30–34 weeks among nine women who developed preeclampsia, one woman with fetal growth restriction, and 20 women with uncomplicated pregnancies from a longitudinal study. Protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Recent proteomic studies have indicated that more than 130 urine proteins could improve timely detection of PE [34]. Patients suffering from PE have a different urine proteomic profile compared to healthy, pregnant patients.…”
Section: Preeclampsia Screening Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent proteomic studies have indicated that more than 130 urine proteins could improve timely detection of PE [34]. Patients suffering from PE have a different urine proteomic profile compared to healthy, pregnant patients.…”
Section: Preeclampsia Screening Methodsmentioning
confidence: 99%
“…Use of serpin A1 alongside albumin proved high accuracy for exposing patients at significant risk of developing PE up to 25 weeks before clinical diagnosis and, thus, indicating severe cases of PE that require immediate delivery [34]. Increased levels of serpin A1 in urine have been linked to the severity of PE [34]. Ceruloplasmin and serpin A7 were also significantly upregulated at 20-24 and 30-34 weeks of gestation in patients who subsequently developed PE.…”
Section: Preeclampsia Screening Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advances in the early detection of women at risk of pregnancy complications have increased in the last decade, in part due to bioinformatic improvements, making it much easier to access and analyze large amounts of data and identify novel biomarkers. Indeed, proteomic biomarkers in maternal urine have proven promising as a non-invasive way of identifying women at risk of preeclampsia and fetal growth restriction [ 6 ]. Proteomic biomarkers, this time in maternal serum samples, were also investigated in a replication study looking at the ratio of IBP4/SHBG proteins as a predictive biomarker for spontaneous preterm birth [ 7 ].…”
mentioning
confidence: 99%